Projection Histogram-Assisted Estimation of Common Phase Error in Coherent Optical OFDM Systems - Zhengxuan Li; Yun Li; Junjie Ma; Jian Chen; Yingxiong Song; Min Wang (IEEE Photonics Journal, 2019)
In this paper, we present a novel blind common phase error estimation method in coherent orthogonal frequency division multiplexing systems using projection histogram-assisted processing. In the proposed algorithm, the constellation of the signal distorted by common phase noise is regarded as a tilted image, which can be rotated back to the right position by tilt adjustment. Considering the characteristics of the constellation, the tilt adjustment can be realized under the assistance of projection histogram. By simply counting and maximizing the number of the projection points fell into certain intervals, the tile angle can be obtained, which means that the common phase error is known. Compared with the conventional blind phase searching method, the proposed method shows similar performance and reduced complexity. Moreover, we optimized the algorithm by dividing the estimation process into two stages, in which case the complexity can be further reduced without introducing bit error ratio penalty.